The effect of plyometric training on the performance of standing broad jump - Chan, Daniel Teck Kian (2019)
Plyometrics are training techniques used by athletes in all types of sports to increase strength and explosiveness. However, plyometric training is not a common training approach in Singapore. This study aims to investigate whether plyometric exercise training can develop power and improve performance in the Standing Broad Jump (SBJ), as a means to arrest the decline on this aspect of fitness amongst youths, before deteriorating to possible premature ambulatory problems in the future for our senior population. Twenty male varsity athletes of various sporting backgrounds aged 21 years and above, participated in this study, of which they were split into two equal groups – A control and treatment. The treatment group underwent a six-week exercise regime which consisted of several plyometric drills. Mann-Whitney U test indicated a positive relationship between SBJ pre-test and post-test results of the treatment group. With a p-value of <0.05, it was deemed statistically significant. In terms of overall mean improvement, both groups displayed an increase in values. However, the treatment group displayed a result of 0.095m as compared to the control group of merely 0.02m. Thus, the significantly greater result justifies this positive relationship between SBJ performance and plyometrics. The greater overall improvement obtained from the results of the SBJ post-tests, denotes that there is a higher positive relationship in treatment than control in the performance of SBJ. Therefore, plyometric training can be used as a successful exercise intervention for improving SBJ performance and surely be used as a means to improve this specific aspect of fitness amongst youths in Singapore.